EEFISIENSI DAN EFEKTIVITAS PENGELOLAAN ZAKAT DI BAZNAS KOTA YOGYAKARTA : : Pendekatan DEA dan Allocation to collection Ratio - Rachma Fadila; Wahyudi, Rofiul; Pribawa E Pantas; Dwi Santosa Pambudi (Mukaddimah: Jurnal Studi Islam, 2023)
Islam is the majority religion in Yogyakarta, with more than 92% of the population following this religion. The potential for zakat in Yogyakarta is enormous. However, the population cannot escape the problem of poverty. This is an opportunity to optimize the role of zakat, infaq, and alms in overcoming poverty in society. To overcome this, Yogyakarta City BAZNAS distributes zakat, infaq, and alms funds to the community. In carrying out its duties, an evaluation is needed to determine the efficiency and effectiveness of the performance of zakat institutions in managing zakat, infaq, and alms funds. This research aims to analyze the efficiency and effectiveness of Yogyakarta City BAZNAS in managing zakat funds in the 2017-2021 period. This research is quantitative. The data type used is secondary data in the form of BAZNAS Yogyakarta City financial report data for 2017-2021. In this research, efficiency measurement uses the Data Envelopment Analysis (DEA) method with a production approach; the Variable Return to Scale (VRS) assumption is output-oriented and measures the level of effectiveness of amyl using the Allocation to Collection Ratio (ACR) method. The input variables used to measure efficiency are current assets, non-current assets, and operational costs. Meanwhile, the output variables used are the collection and distribution of zakat, infaq, and alms funds. To measure the level of effectiveness, the outcome variable used is the target and realization of the distribution of zakat, infaq, and alms funds. This research shows that BAZNAS Yogyakarta City experienced inefficient performance in 2017 and 2018. Inefficiency was 92.9% in 2017 and 98.8% in 2018. Meanwhile, 2019, 2020, and 2021 experienced perfect efficiency according to the measurement results by 100%. To measure the level of effectiveness, in 2018, 2020, and 2021, scores were 88%, 76%, and 81% in the Effective category. In 2017 and 2019, they received the same Highly Effective category with 99% and 90% scores.   Keywords: ACR; BAZNAS; DEA; Efficiency; Effectiveness.